Performance of Peking Ducks (Anas platyrhynchos domesticus L) Given a Mixture of Fermented Sago in the Main Feed - Mustaqim; Wenny Novita Sari; Cut Rauzatul Jannah; Oviana Lisa (SEAS (Sustainable Environment Agricultural Science), 2025)
Ducks are one of the poultry that can be relied on as a source of animal protein, namely meat and eggs, which are greatly needed by the community. Peking ducks are a very potential meat-producing poultry besides chickens. One of the advantages of this poultry is that it has resistance to disease when compared to broiler chickens. More than 19% of egg needs are met from duck eggs, but its role as a meat producer is still low at 0.94%. The low role of ducks as meat producers is caused by inadequate and quite expensive feed. Animal-derived feed ingredients are generally industrial waste, so their nature utilizes waste such as sago pulp. This study aims to investigate the effect of providing fermented sago pulp in rations on the quality of carcasses and abdominal fat of Peking ducks. This study used an experimental method designed with a Completely Randomized Design (CRD), with 4 treatments and 3 replications. The treatments are P1. 100% Bran (Control), P2. 75% Bran + 25% Fermented Sago Pulp, P3. Bran 50% + Fermented Sago Pulp 50%, P4. Bran 25% + Fermented Sago Pulp 75%. Observation parameters in the form of feed consumption, weight gain, feed conversion. The results of the study of providing fermented sago pulp in bran in Peking ducks did not have a significant effect with (P>0.05) on feed consumption, had a very significant effect with (P<0.05) on daily weight gain, did not have a significant effect with (P>0.05) on feed conversion. Treatment P1 (Control) gave the best value for feed consumption, Treatment P4 (Bran 25% + Fas 75%) gave the best value for daily weight gain and treatment P2 (Bran 75% + Fas 25%) gave the best value for feed conversion.